Personagens femininas na ordem patriarcal nos romances de Bernardo Guimarães: Rosaura, A enjeitada, A escrava Isaura e O seminarista - Furlan, Pricila Kátia (2018)
In this research, some characters from the Bernardo Guimarães novels are analyzed: The seminarist (1872), The slave Isaura (1875) and Rosaura, the emjected (1883), highlighting the impact of patriarchal order marks on the existence of the feminine figures of these works . Also analyzed are the characters who hold the patriarchal power, as they are fundamental for the constitution of the plot, as well as revealing the thoughts of the time. This study is done in such a way as to bring works closer to the subjects of contact and also to the differences between them, two interpretative ways that justify this work. Moreover, the novels discussed here - little studied - are revealing of the social issues of the time. We undertake here a bibliographical and theoretical survey and the study of some important characters for the constitution of the plot. Among the central themes of the discussions present in this work, there is matrimony as the physical and economic domain of men over women, issues of the sexual domain by imposition of a masculine power, patriarchal power outlaws (which is also logic within the universe clerical), extending its tentacles on the family and other subjects that revolve around them, the imposition of models of female behavior and the control of the female body, the conditions of life of Afrodescendants, issues related to the misrepresentation of the church and society in relation to women and their rights, and also the influence of factors such as skin color and social condition. It should be emphasized that all these themes occupy the background of the plots on which this analysis stops, given that normally the first plane of the narratives studied here - a common factor in much of the romantic works - contains an impossible love plot. The theoretical basis of this work is linked to the literary, historical and sociological theories of Affonso Romano Sant'Anna, Alfredo Bosi, Benjamim Abdala Júnior, José Verissímo, Gilberto Freyre, Mary Del Priore, Roberto Reis, Roberto DaMatta, Teófilo de Queiroz Junior, Gregory Rabassa, Dante Moreira Leite, Heleieth Saffioti, among other important names.